ANALISIS PERBANDINGAN METODOLOGI SIYASAH SYAR'IYYAH DENGAN USUL AL-FIQH - Abdul Rahman, Mohamad Zaidi (Jurnal Syariah, 2019)
Studies in the field of siyasah shar'iyyah can't be separated from using the same sources of hukm as implemented in the field of U$Ul al-fiqh. This is due to the fact that, hukm is one of the vital elements employed in analyzing siyasah shar'iyyah condition. However, question arises whether the exercise of those sources on U$Ul al-fiqh can be treated similarly on siyasah shar'iyyah. Thus, the aim of this article is to examine whether there is a relationship between siyasah shar'iyyah and U$Ul al-fiqh. On the other hand, the study is trying to explore the dissimilarity of the types of methodology used in both of them.